Negotiating Sharia and Democracy: Institutional Pathways of Political Islam in Aceh - Yusli Effendi; Reza Triarda; Purkon Hidayat (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article examines the transformation of political Islam in Aceh, Indonesia, within the context of decentralized democracy. It traces the evolution of religious governance from insurgency and culturally embedded practices to the establishment of formal judicial and administrative systems. The research draws on qualitative fieldwork conducted in Aceh, combining document analysis, participant observation, field visits, and nine semi-structured interviews with actors from Islamic institutions, political bodies, and civil society organizations. The paper studies the embedding of Sharia into local governance through legal, institutional, and administrative mechanisms. The results show that Aceh’s post-conflict Islamic order developed along three primary trajectories: political reintegration, the codification of ideology into law, and the bureaucratization of religious practices. Sharia is operationalized through qanun legislation, Islamic courts, religious authorities, and enforcement agencies, resulting in a system where moral regulation is embedded within the state apparatus. This configuration enhances political legitimacy and Acehnese identity, yet it also generates challenges related to gender equality, minority rights, and democratic accountability. The article argues that Islamic governance in Aceh arises from institutional compromise rather than ideological dominance, underscoring both the capacity and constraints of political Islam in a pluralist democracy Artikel ini meneroka transformasi Islam politik di Aceh, Indonesia, dalam konteks demokrasi yang terdesentralisasi, dan menelusuri evolusi governansi keagamaan dari fase pemberontakan dan praktik keagamaan kultural menuju pembentukan sistem peradilan dan administrasi formal. Berdasarkan riset lapangan yang dilakukan di Banda Aceh, penelitian ini menggunakan wawancara, analisis dokumen, dan observasi partisipan. Artikel ini juga menelaah bagaimana Syariah dilembagakan dalam pemerintahan lokal melalui mekanisme hukum, institusional, dan administratif. Hasil penelitian menunjukkan bahwa tatanan Islam pasca-konflik di Aceh berkembang melalui tiga trajektori utama: reintegrasi politik, kodifikasi ideologi ke dalam hukum, dan birokratisasi praktik keagamaan. Syariah dioperasionalisasikan melalui legislasi qanun, peradilan Islam, otoritas keagamaan, dan lembaga penegakan hukum, sehingga menghasilkan suatu sistem di mana regulasi moral terintegrasi ke dalam aparatus negara. Konfigurasi ini memperkuat legitimasi politik dan identitas Aceh, namun sekaligus memunculkan tantangan terkait kesetaraan gender, hak-hak minoritas, dan akuntabilitas demokratis. Artikel ini berargumen bahwa governansi Islam di Aceh muncul dari kompromi institusional, bukan dari dominasi ideologis, yang menegaskan kapasitas sekaligus keterbatasan Islam politik dalam demokrasi pluralistik.